MENGEMBANGKAN KREATIVITAS DAN KESADARAN SOSIAL MELALUI KOLASE MEMBATIK - Rade, Desilia Bera; Seran, Antonia Yunita; Sul, Maria Desi Oktavia; Hoar, Anggelina; Woe, Hediana; Surti, Oktaviana; Mau, Maria Gradiana Marice; Bele, Maria Yunitha; Bebe, Apriliana Haryati; Anwar, Muh. Farid Nurul; Rozana, Kardiana Metha; Mitasari, Zuni (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2025)
Banjarejo Village, Ngantang District, Malang Regency, is a village rich in cultural and creative potential. One of the community service programs conducted by Universitas Tribhuwana Tunggadewi (UNITRI) is the introduction of batik collage to students at SDN Banjarejo 03. This activity aims to enhance students' creativity in art while instilling awareness of local cultural heritage. The program employs a hands-on learning approach, where students learn about traditional batik patterns and basic collage techniques to create their own artistic works. The results of this activity show that students are not only able to produce creative batik collage artworks but also develop a deeper understanding of the cultural value of batik and the importance of preserving it. Thus, this program is expected to be an effective way to foster creativity among elementary school children while strengthening their local cultural identity.